THE EFFECT OF USING PICTURE ON STUDENT VOCABULARIES OF NOUN ESPECIALLY IN ANIMAL IN THE V CLASS OF SD SWASTA MUHAMMADIYAH KUTACANE - Cindy Shania; Muhammad Tahir; Raja Fauziah (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This research is aimed to investigate the effect of using picture on student Vocabularies to find out the students’ difficulties in vocabulary by using picture. This is an experimented research design which used the descriptive quantitative method in analyzing the data. The data of this research was the Vth grade students of SD Muhammadiyah Kutacane, Kutacane. In the 2022/2023 academic year by using total sampling methods, 50 students were chosen as the sample. The sample was divided into two groups; 25 students as experimental group and 25 students as control group. The experimental group was given treatment by group using picture vocabularies and control group using direct method. The instrument of the research is written test, which used pre-test and post-test. The result of this research showed that tobserved(16.6 > 2.01) with and df = 48. It means Ha is accepted. Therefore, there were significant effects of using picture vocabularies.